Antagonism and mycoparasitism mechanism of T. harzianum against pathogenic fungus species of F. oxysporum and Capnodium sp. - Mustofa, Ali; Hastuti, Utami Sri (Univeritas Papua, 2024)
The purpose of this study was to test the ability of T. harzianum to inhibit the growth of pathogenic mold species and to determine the effectiveness of T. harzianum mold species in inhibiting the growth of pathogenic molds, as well as investigate how T. harzianum and pathogenic molds interact with each other. The Microbiology Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, State University of Malang, is where this research was conducted. The dual culture method was used for this test by using Czapek Agar (CA) medium. The isolated molds were then incubated for 4x24 hours at 25O–27OC. After that, the antagonism power was calculated. The results of macroscopic and microscopic observations were used to assess the mechanism of T. harzianum mold antagonism against pathogenic molds. The results showed that Trichoderma mold species were more resistant to the pathogenic mold Fusarium oxysporum than the pathogenic mold Capnodium. The antagonistic power of T. harzianum was 80%, with the antagonistic power of Capnodium sp. at 66.7%. The mechanism of mycoparasitism occurs when the hyphae of T. harzianum attach or entangle the hyphae of pathogenic molds, causing damage to the hyphal structure and inhibiting the growth of pathogenic molds.